(untitled) (Texas Journal of Philology, Culture and History, 2023)
In this article, the important role and functions of literature and artistic texts in foreign language classes, the scientific theses of linguists on this topic, and the history of the introduction of literature into foreign languages and the development of foreign language learning competencies through the details of literature in modern foreign language subjects. possibility, how to enrich lessons with them, and according to the results of international research, what artistic texts have been used in high schools in history, or whether students like to work with literature in foreign language classes or not, why literature is needed in foreign language classes in general, and didactic features of working with literary texts are considered in foreign language classes.